Kualitas Pembelajaran Pasca Pandemi Covid-19 Melalui Manajemen Excellent Service Guru Di Sma Islam Al-Azhar 19 Ciracas Jakarta Timur - Hero Gefthi Firnando; Siskandar Siskandar; Akhmad Shunhaji (International Journal Labs, 2022)
The boredom of learning in students while studying from home due to the impact of the Covid-19 pandemic is very concerning, which indicates that there is a lack of excellent service (excellent service) from schools, especially for teachers during the Covid-19 learning period. This concern raises the concern of everyone. Including the Islamic High School Al-Azhar 19 Ciracas, East Jakarta which has made efforts to manage excellent service for teachers so that the quality of learning for students is realized during the post-Covid-19 pandemic. This paper aims to find out how the strategy and implementation of SMA Islam Al-Azhar 19 Ciracas East Jakarta in developing excellent service, especially in relation to improving the quality of learning for students. This paper uses a qualitative research method with a descriptive analytical approach through interviews, direct observations in the field and documentation. Data analysis is obtained from the display which is then reduced, filtered, clarified, data comparison/comparison, parsing, to the final conclusion. The subjects selected in this study were principals, teachers, administrative staff, waka curriculum, parents and students.